If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -16 = 3x + -9 Reorder the terms: -16 + 12x = 3x + -9 Reorder the terms: -16 + 12x = -9 + 3x Solving -16 + 12x = -9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -16 + 12x + -3x = -9 + 3x + -3x Combine like terms: 12x + -3x = 9x -16 + 9x = -9 + 3x + -3x Combine like terms: 3x + -3x = 0 -16 + 9x = -9 + 0 -16 + 9x = -9 Add '16' to each side of the equation. -16 + 16 + 9x = -9 + 16 Combine like terms: -16 + 16 = 0 0 + 9x = -9 + 16 9x = -9 + 16 Combine like terms: -9 + 16 = 7 9x = 7 Divide each side by '9'. x = 0.7777777778 Simplifying x = 0.7777777778
| (13/3)-4-3 | | -(-8x)=(-35) | | 13/3-4-3 | | .25x^2+x+1=0 | | 4(x-5)=6-2x+13+7+2x+2 | | 14x-38=8x+4 | | 26x+21=-23x-9 | | 13x=42+5x | | 100cosx=60 | | r(3-2)=4 | | 2x+8=16+4x | | 27x^3-9x^2+15x= | | 3.7y+9=8.1y-17.4 | | 2x^2+14x+49=9x^2-42x+49 | | 2/9(x-5/4)=-1/9 | | 2x(34)-42=w | | (2x+15)+11x=180 | | 9=-7x | | 3x^2+1ox-77=0 | | (-1-2i)(6-2i)= | | (-5-4i)+(-4+7i)= | | 3x^2+10x-100=0 | | 4x^3-5x+1=0 | | x^2+2x-10=4 | | x^2+2x+10=2 | | x+x+14+x+16= | | 22-3x=58 | | 22-3x=59 | | x+2x=106 | | 4x^2+25y^2+250y+525=0 | | 3x-5=21+x | | 6(c+4)=4c-11 |